Pengaruh Inclusive Leadership dan Job Crafting terhadap Work Engagement dengan Person-Job Fit sebagai Variabel Mediasi - Apritama Nur Hidayat; Fanny Martdianty (Directorate General of Taxes, 2026)
The purpose of this study is to examine the effects of inclusive leadership and job crafting on work engagement, and to test the mediating role of person-job fit. This research aims to determine the influence of inclusive leadership and job crafting on work engagement, and to test the mediating role of person-job fit. The data in this study were collected through an online survey from 376 employees of the Directorate General of Taxes, stationed in DKI Jakarta province. The data were analyzed quantitatively using Structural Equation Modeling (SEM) with the LISREL software. The results of this study prove the positive influence of inclusive leadership and job crafting on work engagement. In addition, it also proves the positive influence of person-job fit on work engagement, the positive influence of inclusive leadership on person-job fit, and the positive influence of job crafting on person-job fit. In the mediation analysis, it was found that person-job fit partially mediates the relationship between inclusive leadership and work engagement. Furthermore, it was also proven that person-job fit partially mediates the relationship between job crafting and work engagement. The results of this study are intended to build organizational attention regarding the creation of work engagement to face organizational changes, especially related to the renewal of the core tax administration system.